Enhanced algal abundance in northwest Ontario (Canada) lakes during the warmer early-to mid-Holocene period. (1st September 2015) - Karmakar, Moumita; Leavitt, Peter R.; Cumming, Brian F.
Abstract: This study investigates regional changes in primary producers in boreal head-water lakes during the warmer early-to-mid-Holocene (EMH) period, across the present-day boreal forest in northwest Ontario, a region that is adjacent to the prairie-forest ecotone. We quantified changes in algal abundance and composition over the Holocene period using pigments, spectrally-inferred chlorophyll a and diatom assemblages in well-dated sediment cores from three lakes. All three indicators showed a coherent pattern of enhanced primary producers in two of the study lakes (Gall Lake and Lake 239) during the EMH, whereas only diatom assemblages suggested higher levels of nutrients in Meekin Lake. Overall, this study supports a regional pattern of enhanced primary producers during the EMH, likely as a function of lower water-levels and warmer temperatures. Elevated concentrations of cyanobacterial pigments also occurred in two of the three lakes during the EMH, whereas pigments from purple-sulphur bacteria provide evidence of enhanced deep-water anoxia in one lake. These findings suggest that future climatic warming in boreal regions could include regional eutrophication and associated increases in cyanobacteria. Highlights: Sediment cores from three head-water lakes were studied over the Holocene. Enhanced abundance of primary producers during early-to-mid-Holocene (EMH). Cyanobacteria blooms also increased during EMH. Time-transgressive changes in primary producers were identified.